Accelerating Radiative Decay in Blue Through‐Space Charge Transfer Emitters by Minimizing the Face‐to‐Face Donor–Acceptor Distances. Issue 12 (2nd February 2022) - Huang, Tianyu; Wang, Qi; Meng, Guoyun; Duan, Lian; Zhang, Dongdong
Abstract: Thermally activated delayed fluorophors (TADF) featuring through‐space charge transfers (TSCT) suffer from low radiative decay rates ( k r s), especially for blue emitters. Here, a xanthene bridge is adopted to construct space‐confined face‐to‐face donor–acceptor alignment and minimize their distances down to 2.7–2.8 Å, even shorter than the interlayer distance of graphite and thus strengthening the electronic interactions. The resulting blue TSCT‐TADF emitters exhibit peaks around ≈460 nm, photoluminescence quantum yields of >90 %, and k r s of nearly 10 7  s −1, almost 2–10 times higher than previously observed values with comparable reverse intersystem crossing rates. The corresponding blue organic light‐emitting diodes show maximum external quantum efficiencies of 27.8 % and 34.7 % with Commission Internationale de L'Eclairage y coordinates of 0.29 and 0.15 using those molecules as emitters and sensitizers, respectively. Abstract : Thermally activated delayed fluorophores are constructed with strong through‐space donor–acceptor interactions by minimizing their face‐to‐face distance of 2.7–2.8 Å, realizing efficient blue emission and fast radiative decay. The materials show maximum external quantum efficiencies of 27.8 % and 34.7 % with relieved efficiency roll‐off and CIE y coordinates of 0.29 and 0.15, when used as emitter and sensitizer in organic light‐emitting diodes.